1983
DOI: 10.1111/j.1464-410x.1983.tb03399.x
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Training—3 Years On

Abstract: Fifty-six patients with the "urge syndrome" were reviewed between 1 and 5 years after in-patient treatment by bladder training. There was an overall initial cure/improvement rate of 85%. The best long-term results were obtained in those with objectively stable bladders before treatment. Forty-three per cent of patients with reduced detrusor compliance and idiopathic instability relapsed after initial improvement. Those with primary instability or with associated degenerative disease responded poorly to treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
9

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 13 publications
0
17
0
9
Order By: Relevance
“…It is sometimes erroneously reduced to the combination of fluid restriction and timed voiding, but actually is a far richer therapy. Holmes et al reported the durability of behavioral therapy to control leakage in overactive bladder patients with initial response rates of 85% and 3-year response rates of 48% [65]. Burgio et al [66] compared their version of behavioral therapy with anticholinergic medication (oxybutynin chloride in titrated doses) in a group of patients with urge and mixed incontinence.…”
Section: Behavior Therapy and Oabmentioning
confidence: 99%
“…It is sometimes erroneously reduced to the combination of fluid restriction and timed voiding, but actually is a far richer therapy. Holmes et al reported the durability of behavioral therapy to control leakage in overactive bladder patients with initial response rates of 85% and 3-year response rates of 48% [65]. Burgio et al [66] compared their version of behavioral therapy with anticholinergic medication (oxybutynin chloride in titrated doses) in a group of patients with urge and mixed incontinence.…”
Section: Behavior Therapy and Oabmentioning
confidence: 99%
“…Most have been based on subjective outcome, and only two have addressed very long-term follow-up after 4 and 6 years; both of these reported much higher success rates than has been our experience [5,11]. Others, however, have reported success rates similar to our own, for example 88% initially reducing to 38% after 6 months [12], and 85% initially reducing to about 50% at 3 years [13]. Although bladder retraining would appear to have limited success (32% of those who replied between 12 and 29 months later) in providing a satisfactory outcome for patients with sensory urgency or detrusor instability, it compares favorably with other treatments for the condition.…”
Section: Discussionmentioning
confidence: 79%
“…One study [6] was in agreement with our observation that there appeared to be no difference in response between those with sensory urgency and those with detrusory instability. Others, however, have suggested that those with stable bladders (sensory urgency) showed the most improvement [8,13,16], with either a poor response [8] or a tendency to relapse [13] in those with detrusor contractions. It is suggested that frequency without instability progresses to reduced compliance and thence to uninhibited contractions [8].…”
Section: Discussionmentioning
confidence: 99%
“…This latter factor has been forgotten by many in their assessment of the treatment. Holmes et al [15] showed that an initial success rate of 85% at 3 months following treatment fell to 50% at 3 years, and on the basis of this suggested that it was perhaps not as good a treatment as was originally thought. We would disagree with this assessment for two reasons.…”
Section: Discussionmentioning
confidence: 95%